Apparent clogging effect in vacuum-induced consolidation of dredged soil with prefabricated vertical drains - Wang, Peng; Han, Yanbing; Zhou, Yang; Wang, Jun; Cai, Yuanqiang; Xu, Fang; Pu, Hefu (Geotextiles and geomembranes, 2020)
The improvement efficiency of a dredged slurry by vacuum preloading is greatly affected by the apparent clogging effect arising during the consolidation process, where the apparent clogging effect refers to the combined impacts of filter clogging and particle blinding around the drain due to particle migration and non-uniform consolidation. Three laboratory model tests with different types of soils were performed to investigate the apparent clogging effect. First, the filter clogging effect was investigated by scanning electron microscopy and cross-plane permeability tests. Second, changes in the particle size distribution due to particle migration were analysed at the micro- and macro-levels, and the particle migration induced blinding effect was assessed through the results of the compressibility and permeability tests. The test results indicated negligible particle migration in pure clay and relatively higher blinding effect in mixture soils. Finally, the effects of blinding due to particle migration and non-uniform consolidation on the overall consolidation rate were theoretically quantified. Both the analytical and tests results implied that the apparent clogging effect is predominantly by non-uniform consolidation rather than the particle migration-induced blinding effect, especially for cohesive marine clay.